Influenza A virus RNA-dependent RNA polymerase: analysis of RNA synthesis in vitro. - Galarza, J M (1996)
Influenza A virus RNA-dependent RNA polymerase, purified from virion ribonucleoprotein particles and from which endogenous genomic RNA (vRNA) has been depleted by treatment with micrococcal nuclease, was used to study transcription initiation, elongation, and termination in vitro. Templates that contained either minus- or plus-sense influenza virus nucleoprotein minigenes with conserved 5' and 3' termini and the uridylate tract were constructed. The dinucleotide ApG and alfalfa mosaic virus RNA4 (AlMV4) were used as primers. ApG primed the synthesis of full-length positive-strand or cRNA products and shorter transcripts, depending upon the molar ratio between the nucleoprotein and the vRNA template. Sequence analysis of the ends of these transcripts demonstrated that the 5' termini of both transcripts and the 3' terminus of the full-length product were complementary to the 3' and 5' termini of the vRNA template, respectively, whereas the 3' terminus of the incomplete product corresponded to a sequence located 40 bases downstream from the 5' terminus of the template and was about 20 nucleotides downstream from the uridylate tract, which is the putative signal for polyadenylation. Binding of the cap structure of AlMV4 by the polymerase activated RNA synthesis by ligation-elongation of small genomic RNA fragments which were likely derived from a genome segment protected by the polymerase from micrococcal nuclease digestion. The sequence of these fragments mapped to a region 14 to 28 nucleotides upstream of the 3' terminus of the viral genome. Polymerase subunit involvement in transcription initiation with ApG or AlMV4 was characterized by studying the effect of purified polyclonal antisubunit immunoglobulins of the G class (IgGs) in transcription assays. These results showed that anti-PB2 IgG inhibited transcription initiation in both ApG- and AlMV4-primed reactions, whereas anti-PB1 antibodies also blocked transcription initiated with AlMV4. The differences observed in product size, product sequence, and differential inhibition by antisubunit IgGs are discussed. These observations would support the notion that the influenza virus RNA-dependent RNA polymerase undergoes a conformational change after the binding of the cap structure of host cell heterogeneous nuclear RNA by PB2, which then usually leads to endonucleolytic cleavage of the capped primer 13 nucleotides downstream from the cap.